Ответы и объяснения

2014-01-10T14:48:12+04:00
7(4-3х)-(8,5-х)=4-3(х-8)28-21х-8,5+х=4-3х+24-21х+х+3х=4+24+8.5-28-17х=8.5х=-0,5
7(4-3х)-(8,5-х)=4-3(х-8)=.
это 2 разных уравнения или как?
одно и тоже
2014-01-10T14:54:18+04:00
7(4-3X)-(8,5-X)=4-3(X-8)
   28-21X-8,5+X=4-3X+24
      28-8,5-24-4=-3X-X+28X
                  -8,5=17X
                      X=17/8,5
                      X=2
7(4-3X)-(8,5-X)=4-3(X-8)
28-21X-8,5+X=4-3X+24
28-8,5-24-4=-3X-X+28X
-8,5=17X
17х=-8,5
теперь -8,5 разделить на 17,а не 17 разделить на -8,5
х=-0,5